Buried secrets - West, Carly Anne; Heitz, Tim; Artful Doodlers Ltd ([New York] Scholastic Inc, 2019)
"Nicky Roth should be happy--he's finally proven that his best friend, Aaron, and Aaron's younger sister, Mya, are missing. Better yet, the police are actually doing something: they've plastered the town with missing posters, and have organized weekend search parties for the kids. But Nicky can't seem to pry his eyes from the house across the street, especially after he sees a frantic SOS coming from Aaron's room in the Peterson house. After what happened in the winter, and the warnings they got from their parents, Nicky's friends insist they can't help him investigate his neighbor anymore. If Nicky wants to find out what's going on in the Peterson house, he's going to have to do it alone"--Amazon
Crime & mystery
Keywords: Detective and mystery stories; Friendship -- Juvenile fiction; Horror tales; Missing persons -- Investigation -- Juvenile fiction; Neighbors -- Juvenile fiction; Nightmares -- Juvenile fiction; Family secrets -- Fiction; Friendship -- Fiction; Horror stories; Missing persons -- Fiction; Neighbors -- Fiction; Detective and mystery stories; Friendship; Horror tales; Missing persons -- Investigation; Neighbors; Nightmares; Horror tales; Young adult fiction; Detective and mystery fiction; Detective and mystery fiction; Fiction; Horror fiction; Horror fiction; Horror tales; Juvenile works; Mystery fiction; Young adult works